The role of non-thermal atmospheric pressure biocompatible plasma in the differentiation of osteoblastic precursor cells, MC3T3-E1 - Han, Ihn (Oncotarget, 2017)
Non-thermal atmospheric pressure plasma is ionized matter, composed of highly reactive species that include positive ions, negative ions, free radicals, neutral atoms, and molecules. Recent reports have suggested that non-thermal biocompatible plasma (NBP) can selectively kill a variety of cancer cells, and promote stem cell differentiation. However as of yet, the regulation of proliferation and differentiation potential of NBP has been poorly understood. Here, we investigated the effects of NBP on the osteogenic differentiation of precursor cell lines of osteoblasts, MC3T3 E1 and SaOS-2. For in vitro osteogenic differentiation, precursor cell lines were treated with NBP, and cultured with osteogenic induction medium. After 10 days of treatment, the NBP was shown to be effective in osteogenic differentiation in MC3T3 E1 cells by von Kossa and Alizarin Red S staining assay. Real-time PCR was then performed to investigate the expression of osteogenic specific genes, Runx2, OCN, COL1, ALP and osterix in MC3T3 E1 cells after treatment with NBP for 4 days. Furthermore, analysis of the protein expression showed that NBP treatment significantly reduced PI3K/AKT signaling and MAPK family signaling. However, p38 controlled phosphorylation of transcription factor forkhead box O1 (FoxO1) that related to cell differentiation with increased phosphorylated p38. These results suggest that non-thermal atmospheric pressure plasma can induce osteogenic differentiation, and enhance bone formation.